Changes of Mineralogical Properties and Biological Activities of Gypsum and Its Calcined Products with Different Phase Structures. (10th March 2021) - Liu, Kaiyang; Han, Shu; Gao, Wei; Tang, Ya'nan; Han, Xitao; Liu, Ziqin; Bao, Liyuan; Zhi, Meiru; Wang, Hongyue; Wang, Yingli; Du, Hong
Abstract : Raw gypsum (RG) and calcined gypsum (CG) are widely used in traditional Chinese medicine (TCM). RG is usually taken orally to resolve heat and diminish inflammation, while CG is only used externally to treat ulcerations and empyrosis. Calcination at different temperatures, three phase CG structures, namely, bassanite, anhydrite III, and anhydrite II, may be generated. We herein investigated the relationship between the phase structure and the efficacy of CG and the optimum phase structure for CG. RG has a compact structure, small pore size, weak anti-inflammatory effect, but no antibacterial effect, and has almost no effect on the repair of scalds. CG150 (bassanite) has a loose texture, large pore size and specific surface area, and certain antibacterial and anti-inflammatory effects, but it has a poor repair effect on scalds. CG750 (anhydrite II) has a compact structure, small pore size and specific surface area, and low antibacterial and anti-inflammatory effects, but it has a certain repair effect on scalds. Only CG350 (anhydrite III) has good performance in texture, pore size, specific surface area, antibacterial, anti-inflammatory, and scald repair. Our research has proved that the mineral properties and biological activities of CG are different due to different phase structures. CG350, namely, anhydrite III, is considered by our research to be the optimal phase structure as CG.